Kekerasan Terhadap Perempuan dalam Novel Kupu Wengi Mbangun Swarga Karya Tulus Setiyadi (Kajian Feminisme Sastra) - Rofiqoh, Rieskie Ari; Zaidah, Nuning; Werdiningsih, Yuli Kurniati (Universitas PGRI Semarang, 2021)
The purpose of writing this research is to describe violence against the main female character in Kupu Wengi Mbangun Swarga Tulus Setiyadi's book. The formulation of the problem in this research is how the form of violence against the main female character in the novel Kupu Wengi Mbangun Swarga. The method in this research is qualitative, using the theory of feminism which focuses on the violence of the female main character. The research data is in the form of words, phrases, sentences and discourses that contain elements of violence against female characters in the novel Kupu Wengi Mbangun Swarga. The data collection technique is done by reading and recording data quotations that contain forms of violence against the female main character in the novel Kupu Wengi Mbangun Swarga. After the data is collected, data analysis techniques are carried out by reducing data, displaying data and conclusions or verification. The results showed that there were three forms of violence against female figures, namely psychological violence, physical violence and sexual violence. As for the perpetrators of oppression against the main female character, it is carried out by male and female figures.Â